PREFERRED ATTRIBUTES OF EMPLOYER BRAND ATTRACTIVENESS AMONG POTENTIAL EMPLOYEES IN THE HOTEL INDUSTRY - Ognjanović, Jasmina (The European Journal of Applied Economics, 2021)
Human resources have a particularly important role in the hotel business since the hotel industry is a labor-intensive industry. As key resources for creating value and the company’s image, employees should be provided with appropriate tangible and intangible benefits to affect their efficiency. On the other hand, the hotel industry does not have the image of an attractive employment industry. For this reason, it is necessary to identify the potential benefits to current employees and potential employees in hotels in order to achieve better work results. The research objective is to examine the preferred attributes of employer brand attractiveness among potential employees in the hotel industry. By analyzing the results, we conclude that the preferred attributes of employer brand attractiveness are career advancement and development and employee training and development. Employees’ desire to work for an employer that provides employee training and development opportunities brings numerous benefits to hotels, since employee development contributes to the development of high-quality hotel services, more efficient employees, and, thus, better organizational performance. The least preferred attributes of employer brand attractiveness among potential hotel employees are “corporate reputation” and “corporate culture”.
Keywords: employer brand attractiveness, human resource, attributes of employer brand attractiveness, hotel